Direct recycling of aluminium 6061 chip through cold compression - Chan, B.L.; Lajis, M.A. (Engg Journals Publications, 2015)
Aluminium is globally used in many different ways, from beverages cans to a large aircraft. This is due to aluminium’s remarkable mechanical properties as the same time having a low density. The high usage of aluminium in the everyday life, encourage higher production of aluminium where high energy consumption manufacturing process such as melting bauxite for primary material or melting recycled aluminium conventionally for secondary aluminium. So by directing recycling the aluminium chip through cold compression will reduce the energy consumption during the manufacturing process. In this process the aluminium chipwere compressed at maximum of 45 tons force with a set amount of holding time. The compressed specimens were then strengthening through sintering. Through sintering, the Ultimate tensile strength (UTS) of the specimen increased but at the same time micro-hardness and the density is sacrifice. On the other hand, the Elongation to failure (ETF) reduced due to the high compression force which exceeded the optimum. Further deformation process which involved shearing would be recommended to further improve the overall properties.